Ultra goes to war : the secret story - Lewin, Ronald (London : Hutchinson, 1978)
Relying upon his memory and some government documents the author examines Ultra, the intelligence network that intercepted German radio transmissions and broke their coded contents during World War II.
The glow-lamp machine -- The British breakthrough -- A plan called Smith -- Station X -- The secret Limeys -- The Mediterranean shores -- Mr Churchill's secret source -- Ultramarine -- The American involvement -- Alamein to the Alps -- Overture and beginners: the prelude to D Day -- Finale and curtains: from D Day to victory.
Includes bibliographical references (pages 379-383) and index.
Keywords: 1939-1945; World War, 1939-1945 -- Great Britain; Guerre mondiale, 1939-1945 -- Service secret -- Grande-Bretagne.; Great Britain